2019
DOI: 10.1038/s41590-019-0549-0
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput phenotyping reveals expansive genetic and structural underpinnings of immune variation

Abstract: By developing a high-density murine immunophenotyping platform compatible with highthroughput genetic screening, we have established profound contributions of genetics and structure 19 co-corresponding authors. Data and Code AvailabilityThe flow cytometry files that support the findings of this study are available from www.flowrepository.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Considering the links previously suggested between immune cell development, immune homeostasis, and the microbiome 12 , we considered the developing intestinal microbiome as a potential driver of these changes in immune profile. Similarly, many immune parameters are sexually dimorphic, at least in mice 13 . Hence, we also considered the influence of sex on these developing immune profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the links previously suggested between immune cell development, immune homeostasis, and the microbiome 12 , we considered the developing intestinal microbiome as a potential driver of these changes in immune profile. Similarly, many immune parameters are sexually dimorphic, at least in mice 13 . Hence, we also considered the influence of sex on these developing immune profiles.…”
Section: Resultsmentioning
confidence: 99%
“…A smaller body size (and thus total blood volume) undoubtedly contributed to the increased pulmonary metastatic burden we observed, as well as the presence of extrapulmonary metastases (bone marrow, liver, kidney). However, it was recently shown that Duoxa2 mutant mice have alterations in key immune cell subsets (CD4+ T-cells, neutrophils, monocytes and NK cells) (Abeler-Dorner et al 2020), which could also account for their increased metastatic colonisation. Thus, generation of an inducible Duoxa2 mutant mouse, wherein Duoxa2 could be deleted in an adult mouse, will be required to disentangle any effects that loss of DUOXA2 may be having on metastatic colonisation aside from a smaller body size.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do play an import role in mammalian cells as Dph1 null mice display multiple developmental defects that parallel Miller-Dieker syndrome (MDS) (Yu et al 2014), associated with deletions on chromosome 17p13.3, Dph3 null mice are embryonically lethal (Liu et al 2006) and Dnajc24 ( Dph4 ) null mice almost always die before birth with the few that do survive showing severe developmental defects reminiscent of Dph1 null mice (Webb et al 2008). Recently, Dph6 mutant mice were shown to have an immune phenotype with alterations in many innate and adaptive cell lineages (Abeler-Dorner et al 2020), and it is possible that these may be affecting metastatic colonisation. Thus, as very little is known about ABHD17A and DPH6 in the context of cancer, it is difficult to precisely speculate how they may be playing a role in tumour cell extrinsic regulation of metastatic colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they do play an import role in mammalian cells as Dph1 null mice display multiple developmental defects that parallel Miller-Dieker syndrome (MDS) (Yu et al 2014), associated with deletions on chromosome 17p13.3, Dph3 null mice are embryonically lethal (Liu et al 2006) and Dnajc24 (Dph4) null mice almost always die before birth with the few that do survive showing severe developmental defects reminiscent of Dph1 null mice (Webb et al 2008). Recently, Dph6 mutant mice were shown to have an immune phenotype with alterations in many innate and adaptive cell lineages (Abeler-Dorner et al 2020), and it is possible that these may be affecting metastatic colonisation. Thus, as very little is known about ABHD17A…”
Section: Protein Modificationmentioning
confidence: 99%
“…These genes regulate pulmonary metastatic colonisation primarily by impacting on the function of the haematopoietic/immune system (lymphocytes, granulocytes/monocytes and platelets). In addition, Bach2 was also a 'hit' in our screen, showing decreased metastatic colonisation, and Bach2 is a key regulator of CD4 + T-cell differentiation(Roychoudhuri et al 2013), with Bach2 mutant mice recently being shown to have increased CD8 + T-cell cytotoxic activity(Abeler-Dorner et al 2020). Indeed, phenotypic analysis of the 34 metastatic colonisation regulating genes detailed in this study show a strong enrichment for genes involved in immune/haematopoietic system development and function with phenotypes in those categories representing 88% of all the reported phenotypes associated with those genes.…”
mentioning
confidence: 95%